1991
DOI: 10.1017/s0022215100115300
|View full text |Cite
|
Sign up to set email alerts
|

CT of the paranasal sinuses and functional endoscopic surgery: a critical analysis of 100 symptomatic patients

Abstract: CT scans of 100 patients from the Rhinology Clinic at the Royal National Throat, Nose and Ear Hospital were reviewed in order to test the precepts forming the basis of functional endoscopic sinus surgery, especially as they relate to the radiological investigation. These were: (a) the site of origin of sinus infection. (b) The relevance of certain anatomical variants in the middle meatus to sinus infection and (c) The use of CT as the radiological method of diagnosis in all cases.Obstruction in the middle meat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
93
3
11

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 148 publications
(115 citation statements)
references
References 10 publications
(13 reference statements)
8
93
3
11
Order By: Relevance
“…(Table 5 In our study, uncinate pneumatization was seen in 12 (11.3%) cases of which 10 (9.43%) were bilateral and only 02 (1.89%) were on the right side. These findings correlated to Lloyd GAS et al, (1991) who reported 16 % cases of uncinate pnuematization [25].…”
Section: Discussionsupporting
confidence: 89%
“…(Table 5 In our study, uncinate pneumatization was seen in 12 (11.3%) cases of which 10 (9.43%) were bilateral and only 02 (1.89%) were on the right side. These findings correlated to Lloyd GAS et al, (1991) who reported 16 % cases of uncinate pnuematization [25].…”
Section: Discussionsupporting
confidence: 89%
“…3,4 Lloyd et al have stated that when CB occupies the space between the septum and the lateral nasal wall, there may be total impediment of the middle meatus orifice. 14,15 In our study we found that there was no significant relation between presence of concha bullosa and occurrence of sinusitis even on segregating the data for comparing type of concha bullosa with occurrence of sinusitis no significant relation was found. One of the drawbacks of the present study was that the concha bullosa dimensions were not taken into account.…”
Section: Discussioncontrasting
confidence: 54%
“…In practice, interviews concerning the causal relation, frequency, latent period and atopic disposition often provide suggestions but sometimes give unreliable evidence to base the diagnosis of occupational nasal allergy. Therefore, nasal provocation tests (144,(1314)(1315)(1316)(1317) are necessary to confirm the causality between the disease and any work exposure (1390 Computerized tomography has become the principal radiological investigation for major sinonasal disorders but is of limited use in the diagnosis of allergic rhinitis (1392)(1393)(1394)(1395)(1396). Computerized tomography scans can be carried out after receiving specialist advice:…”
Section: Diagnosis Of Inhalant Allergymentioning
confidence: 99%